INFLUENCE OF HEPARINOID FROM PAEONIA LACTIFLORA ON HEMOSTATIC SYSTEM WITHIN CONDITIONS OF PRETHROMBOSIS - M. G. Lyapina (Farmaciâ i Farmakologiâ (Pâtigorsk), 2019)
The search and development of direct and rapid anticoagulants used per os, is an urgent problem in physiological and medical science. A number of plants contain heparin-like components with a positive effect on the hemostatic system, both within normal and in some pathological conditions of the body.The aim of the work was to study the complex effect of fibrin, a heparin-like substance (heparinoid) from the roots of Paeonia lactiflora, on fibrinolytic, anticoagulant systems of the body and polymerization processes, when it is administered per os in animals within normal conditions and when modeling the state of prethrombosis.Materials and methods. To carry out the research, the roots of Paeonia lactiflora growing in the Botanical Garden of Moscow State University, and laboratory animals – male Wistar rats – were used. To study the antithrombotic effects of the extract from roots containing heparinoid, the state of prethrombosis was modeled in rats. The determined parameters of hemostasis were: anticoagulant activity according to the tests of activated partial thromboplastin time and thrombin time, fibrinolytic activity according to the test of total fibrinolytic activity, fibrin polymerization according to the test of fibrindepolymerization activity of blood plasma.Results. With repeated (every 24 hours within 3 days) oral administration of the extract containing heparinoid, in animals within normal conditions and with prethrombosis, the following anticoagulant effects were established in the blood: an increase in anticoagulant, fibrindepolymerization and fibrinolytic plasma activity. Possible mechanisms of the activating effect of heparinoid on fibrinolysis and anticoagulant properties of plasma due to the excretion of tissue plasminogen activator into the bloodstream from the endothelium, thrombin inhibition, and fibrin polymerization are described. Moreover, the anticoagulant effect of the use of the extract from the peony roots was equivalent to that of the reference drug of low molecular weight heparin from Celsus (USA). For the first time, it was revealed that when modeling experimental prethrombosis, the administration of heparinoid in rats at the dose of 37.5 IU/kg МЕ/кг body weight restored impaired hemostasis, which requires a further study.Conclusion. The ability of heparinoid from peony roots to normalize the functional state of the anticoagulant system during the development of prethrombosis in animals has been established. The restriction of fibrin polymerization during oral administration of heparinoid from peony in animals by increasing the enzymatic fibrinolytic and fibrindepolymerization activity of blood plasma was revealed. In the future, heparinoid can be used as an antithrombotic agent.